4x-6 = -6x-4
4x+6x = 6-4
10x = 2
x = 2/10
x = 1/5
Regards,
A Pakistani!
Chat with our AI personalities
x=3
6x - 3y = 304x = 2 - y4x = 2 - yy = 2 - 4x (substitute 2 - 4x for y into the first equation)6x - 3y = 306x - 3(2 - 4x) = 306x - 6 + 12x = 3018x = 36x = 2y = 2 - 4x (substitute 2 for x)y = 2 - 4(2) = 2 - 8 = -6So the solution is x = 2, and y = -6.x + y = 2 + -6 = -4Thus, it is true that x + y = -4.
2x-4=6x+8-8= -82x-12= 6x-2x= -2x-12= 4x/4=/4-3=x
y = 4x + 6As there are two unknowns, you need to have two equations to solve this out.Else you can simple write the values of x and y as:4x = y - 6x = (y - 6) / 4
It is an equation and the value of x is 4